2009
DOI: 10.1177/0731684408099415
|View full text |Cite
|
Sign up to set email alerts
|

Development of Recycled Polypropylene Matrix Composites Reinforced with Fly Ash

Abstract: Utilization of recycled polypropylene obtained from post-consumer products and fly ash particles, obtained as a by-product from thermal power plants, has environmental as well as economical benefits for society. A valuable addition can be made to these waste materials by converting them into composite materials. In this study, an attempt has been made to develop a composite material from RPP and fly ash in 1 : 1 weight ratio, using two types of coupling agents. A silane coupling agent (VTMO) and a maleated pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…As discussed earlier, the presence of the coupling agent influenced the interfacial bonding and the mechanical properties of the composites. The use of the conventional silane coupling agent in the FA/R matrix was studied earlier, where it was reported that a 6 wt % Dynasylan VTMO‐treated composite showed increases of 4 and 15% in the flexural strength and modulus, respectively, in comparison with the untreated ones . When compared with silane coupling agents, these long‐chain fatty acids, that is, stearic, palmitic, and ester FP, LA has been found to render efficient coupling action at a lower percentage that is, at 2 wt %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed earlier, the presence of the coupling agent influenced the interfacial bonding and the mechanical properties of the composites. The use of the conventional silane coupling agent in the FA/R matrix was studied earlier, where it was reported that a 6 wt % Dynasylan VTMO‐treated composite showed increases of 4 and 15% in the flexural strength and modulus, respectively, in comparison with the untreated ones . When compared with silane coupling agents, these long‐chain fatty acids, that is, stearic, palmitic, and ester FP, LA has been found to render efficient coupling action at a lower percentage that is, at 2 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…Das et al reported the use of R through the formation of composites with a 50 wt % loading of FA with vinyl trimethoxyl silane (VTMO) and maleated PP (Epolene G3003) coupling agents. The mechanical properties and thermal stability were found to be much higher in the VTMO‐treated composites compared to the untreated ones because of enhanced interaction at the filler–matrix interface in the presence of VTMO .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A remarkable result is the value obtained for maximum strength regarding M2 sample, that results + 36% higher than the one of pure PP. Other researchers observed an improvement of flexural strength in PP as a function of fly ash (coal fly ash) addition with a maximum improvement of about + 20% at 30 wt % filler content …”
Section: Resultsmentioning
confidence: 88%
“…6 Searching for an improvement in another study, K. Das et al tested two different types of commercial CAs for post-consumer PP reinforced with fly-ash (Si oxide based byproduct from thermal power plants); they obtained 15% in modulus and 9.5% in strength increments with a silane based coupling agent (Dynasylan VTMO); they reported the benefit of the chemical interaction between the Si oxide based filler and the silane coupling agent. 7 Regarding ecological fillers, due to their useful characteristics, discarded natural fibers 8 have been used in different fields of polymeric materials as reinforcing agents for decades. [9][10][11][12][13][14] However, the lack of interaction between hydrophobic polymers and cellulosic fibers makes fiber dispersion difficult during the mixing process.…”
Section: Introductionmentioning
confidence: 99%